Mikirecco of Shekacho: Rethinking The Indigenous System of Governance and Uncovering Its Democratic Features - Admasu Adraro Akako; Wasihun Bezabih Bekele; Ehadig Geda Goda (Universitas Sultan Ageng Tirtayasa, 2023)
The purpose of this study is to explore the Indigenous System of Governance of Shekacho Community in Sheka Zone, South West Ethiopia. Pertinent to this, a qualitative approach—a key informant interview—was employed. Applicable to this, the purposive sampling technique was used to select research participants. Accordingly, information was gathered primarily using key informant interviews and FGD. The deductive thematic analysis technique was employed for the analysis of the data. The following conclusion was drawn from the analysis made. The findings indicated that the indigenous system of governance of the Shekacho community is one of the longest-lived, having its own distinctive nature and structural hierarchy through which socio-political and economic affairs of the community are carried out. The issue of social cohesion and social welfare, which are embedded in the customary norms and values of the community, is one of the magnificent pillars of the indigenous system of governance of Shekacho community. Therefore, it plays an irreplaceable role in maintaining social stability and cohesion. The indigenous system of governance of Shekacho people substantially includes democratic elements that can consolidate democracy at the national level. Therefore, recognizing the indigenous system of governance can have a tremendous role in promoting democracy in Ethiopia at large.